Semiautomatic object-space road extraction combining a stereoscopic image pair and a TIN-Based DTM - Martins, Erico F. O.; Dal Poz, Aluir P. [UNESP]; Gallis, Rodrigo A. B. (Ieee-inst Electrical Electronics Engineers Inc, 2015)
In this letter, a semiautomatic method for road extraction in object space is proposed that combines a stereoscopic pair of low-resolution aerial images with a digital terrain model (DTM) structured as a triangulated irregular network (TIN). First, we formulate an objective function in the object space to allow the modeling of roads in 3-D. In this model, the TIN-based DTM allows the search for the optimal polyline to be restricted along a narrow band that is overlaid upon it. Finally, the optimal polyline for each road is obtained by optimizing the objective function using the dynamic programming optimization algorithm. A few seed points need to be supplied by an operator. To evaluate the performance of the proposed method, a set of experiments was designed using two stereoscopic pairs of low-resolution aerial images and a TIN-based DTM with an average resolution of 1 m. The experimental results showed that the proposed method worked properly, even when faced with anomalies along roads, such as obstructions caused by shadows and trees.
Keywords: Dynamic programming (DP); Road model; Stereoscopic aerial images; 3-D road extraction